Comparative study of the effects of sclerosing substances in the production of pleural symphysis - Girardi, Gino; Filpi, Mariela; Fernández, Ricardo; Keuchkerián, Marcel; Pose, Juan; Giossa, Walter; Chiossoni, Marta; Laca, Elisa (Cirugía del Uruguay, 1991)
The production of pleural symphisis is proposed as a practica/ solution to recidivistic malign pleuresy. In arder to make a controlled prospective and comparative study, the author designed a model that tests two alkaline substances using sodium hydroxide and terramycin and a control group (distillate water).